2021
DOI: 10.1186/s12891-021-04331-4
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and education for community-dwelling older participants with knee osteoarthritis: a video-linked programme protocol based on a randomised controlled trial

Abstract: Background Neuromuscular and quadriceps exercises have been shown to be effective approaches to relieve pain and to improve function for patients with knee osteoarthritis. In this study, we aim to provide an informative feasible model in which therapeutic exercise and education will be undertaken with physiotherapy supervision and instruction via video link. We also aim to explore the relationship between program-induced pain alleviation/functional improvements and reduction in irritability, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…Three studies focused on patients with obesity and knee OA [21,24,25]. In terms of mHealth and the apps evaluated, 7 studies included mHealth or apps on exercise therapy such as strength training [20][21][22][23][24]26,27], 6 involved patient education [20][21][22][23]25,26], and 2 were related to dietary advice [21,25]. Word clouds generated by the titles and abstracts of the 8 studies are shown in Multimedia Appendix 2, and a summary of our findings is shown in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies focused on patients with obesity and knee OA [21,24,25]. In terms of mHealth and the apps evaluated, 7 studies included mHealth or apps on exercise therapy such as strength training [20][21][22][23][24]26,27], 6 involved patient education [20][21][22][23]25,26], and 2 were related to dietary advice [21,25]. Word clouds generated by the titles and abstracts of the 8 studies are shown in Multimedia Appendix 2, and a summary of our findings is shown in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…The years of publication of the included studies were 2017 (n=1) [22], 2019 (n=1) [20], 2020 (n=3) [23,25,26], and 2021 (n=3) [21,24,27]. There were 3 randomized controlled trials (RCTs) [21,23,24], 4 RCT protocols [22,[25][26][27], and 1 conference abstract on an RCT [20]. The studies were conducted in the United States, the Netherlands, Germany, Australia, Turkey, China, Pakistan, and Taiwan.…”
Section: Resultsmentioning
confidence: 99%
“…The years of publication of the included studies were 2017 (n=1) [ 22 ], 2019 (n=1) [ 20 ], 2020 (n=3) [ 23 , 25 , 26 ], and 2021 (n=3) [ 21 , 24 , 27 ]. There were 3 randomized controlled trials (RCTs) [ 21 , 23 , 24 ], 4 RCT protocols [ 22 , 25 - 27 ], and 1 conference abstract on an RCT [ 20 ]. The studies were conducted in the United States, the Netherlands, Germany, Australia, Turkey, China, Pakistan, and Taiwan.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies focused on patients with obesity and knee OA [ 21 , 24 , 25 ]. In terms of mHealth and the apps evaluated, 7 studies included mHealth or apps on exercise therapy such as strength training [ 20 - 24 , 26 , 27 ], 6 involved patient education [ 20 - 23 , 25 , 26 ], and 2 were related to dietary advice [ 21 , 25 ]. Word clouds generated by the titles and abstracts of the 8 studies are shown in Multimedia Appendix 2 , and a summary of our findings is shown in Tables 1 and 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The exercise process requires community administrators and family members to supervise and provide any support. During telerehabilitation, participants will have opportunities to communicate with their peers in a community setting, thereby promoting willingness and motivation to participate through mutual encouragement [ 50 ]. Besides, performing neuromuscular training at home saves patients’ time commuting to hospitals.…”
Section: Discussionmentioning
confidence: 99%